Response of Two Rosa sp. to Light Quality in Vitro. - Al-Rekaby, Layth Sareea (Iraqi Journal of Science, 2023)
In this study, dark and various light qualities (white, red, green, and blue) were applied to evaluate their effects on growth characteristics, chemical content, and callus characteristics of Rosa damascene Mill. and Rosa hybirda L.   Explant (single-node and shoot tips) cultured on MS media supplemented with sucrose, agar, and plant growth regulators ( Kin 0.5 mg/l and IBA 1 mg/l for whole plant formation experiment or 1 mg/l kin with 0.5 mg/l IBA for callus experiment), incubated in a growth chamber.   The results of the whole plant formation experiment showed variation in growth characteristics in two types of Rosa, Green and white light caused the height ratio of shoot growth compared with dark, while red and green light caused the height ratio of root growth to compare with dark. Rosa growing in white or green has a higher content of chlorophyll, as well as carbohydrates and proteins in shoot and root parts compared with dark.   The results of the callus experiment explained variation in callus characteristics (shape, texture, color, and weight), the highest fresh weight (1.83 and 1.99) gm and dry weight (0.207 and 0.233) mg of callus Rosa damascene and Rosa hybirda, respectively in dark conditions compared with least in blue light.